Training and expertise in undertaking assisted vaginal delivery (AVD): a mixed methods systematic review of practitioners views and experiences - Claire Feeley; Nicola Crossland; Ana Pila Betran; Andrew Weeks; Soo Downe; Carol Kingdon (BMC, 2021)
Plain language summary During the late stages of childbirth, complications can occur which require rapid birth of the baby. This can be facilitated with instruments (usually forceps or a suction cup) or by surgery (caesarean section). In some circumstances, instrumental birth (also termed assisted vaginal delivery, AVD) may be a better option than caesarean section. AVD requires practitioners to develop skills, competence and expertise in the procedure. Our aim for this review was to examine practitioners', funders' and policy makers' views about competence and expertise in AVD, how they can best gain this, the barriers and facilitators to implementing training packages, and their views, opinions and perspectives of their training. We included 27 studies (published 1985-2020), mostly from high-income countries. We had moderate confidence on one findings statement, with the rest assessed with low confidence. We found that practitioners valued extra training in AVD, observing others using the different instruments, and opportunities for clinical supervision, mentorship to gain experience, competence and expertise. We also found that, from the practitioners' perspective, competence encompasses a number of inter-related skill sets; non-technical skills (e.g. effective communication with the labouring woman), broad clinical skills (e.g. capacity to assess the whole clinical picture) and technical instrumental skills (e.g. correct application of a vacuum cup to the fetal head, or capacity to turn the baby so it is in the right position). Practitioners also identified a number of barriers and facilitators that supported (or did not support) their training needs and development.